Konkurencja na rynku detalicznym energii - znaczenie unbundlingu - Kozak, Małgorzata (Competition on the Energy Retail Market - Role of Unbundling, 2008)
According to the provisions of the Directives 2003/54/EC and 2003/55/EC all EU member states shall ensure that from 1 July 2007 the eligible customers are all energy customers, which means that on that day full opening of the electricity and gas markets will take place in the countries that will not have liberalized their markets fully. Giving to all energy end-users the right to choose their suppliers was preceded by various actions aimed to limit the domination of natural monopolies (energy companies were mostly vertically integrated or bundled the way that hindered new entries). The measures taken, enforced by the provisions of the Directives mentioned above, were for example the obligation to unbundle the activity of a transmission system operator as well as a distribution system operator from the structure of a vertically integrated company. Effective unbundling is crucial for the creation and development of competition in the retail segment. The data presented in the following working paper that refers to unbundling and customer switching in the EU member states that fully opened their energy markets in 1998-2005 as well as problems faced by market players (limited availability of information, practical ability to exercise the right to switch for the supplier of the customer's choice, problems with data handling in the companies bundled with the system operators) fully confirm the aforementioned conclusion. While the observations done for the energy market indicate that the most efficient is the ownership unbundling. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 345-357